2020
DOI: 10.1176/appi.neuropsych.19030058
|View full text |Cite
|
Sign up to set email alerts
|

Functional Motor Symptoms in Parkinson’s Disease and Functional Parkinsonism: A Systematic Review

Abstract: Whereas functional symptoms are common in Parkinson's disease (PD), a parkinsonian syndrome may occasionally reflect a pure functional disorder (also named functional parkinsonism [FP]). This review aimed to decipher these entities to clarify the link between functional manifestations and PD.Methods: Following the PRISMA guidelines, the authors performed a systematic literature search of the PubMed and Science Direct databases for the period 1988 to December 2018 to identify studies of patients with either FP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 40 publications
2
28
0
1
Order By: Relevance
“…The same network abnormalities, together with abnormal overweighting of prior expectancies about symptoms might distort sensory perception [33] and contribute to the development of comorbid FMDs. We do not have enough evidence to explain the occurrence of FMDs before PD, but it is likely that functional symptoms arise through the same network [34] and neurochemical abnormalities [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same network abnormalities, together with abnormal overweighting of prior expectancies about symptoms might distort sensory perception [33] and contribute to the development of comorbid FMDs. We do not have enough evidence to explain the occurrence of FMDs before PD, but it is likely that functional symptoms arise through the same network [34] and neurochemical abnormalities [4].…”
Section: Discussionmentioning
confidence: 99%
“…A prospective study found that 19.6% and 8.9% of patients assessed in the emergency department had comorbid functional symptoms in addition to stroke and migraine, respectively [9]. A recent systematic review showed that onset of functional symptoms often predated or occurred at the same time as PD diagnosis and was more likely to involve the side most affected by parkinsonism [4]. Another systematic review highlighted a 12% frequency of paroxysmal non‐epileptic seizures (PNES) in subjects with a primary diagnosis of epilepsy [10], whereas the reported rate of epilepsy among a large sample of people with a primary diagnosis of PNES was 5.3% [11].…”
Section: Introductionmentioning
confidence: 99%
“…To note, there was a tendency towards older age at onset in movement disorders, notably in patients with functional parkinsonism (mean: 48.3 years old). In a recent literature review, the mean age at onset in functional parkinsonism was 45.6 years (Ambar Akkaoui et al 2020). On the contrary, age at onset was lower in functional dystonia (mean: 35.2), and this is also in agreement with a previous study that found age at onset of 29.6 years old in functional dystonia.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that some phenotypes affect more one gender or one age range. For example, previous studies suggested that functional myoclonus affects more men (55%)(van der Salm et al 2014), while functional parkinsonism is more frequent in older patients (Ambar Akkaoui et al 2020). Some controversies also exist about FMD affecting more the left side of the body (J.…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal deposit of insoluble proteinaceous material amyloid beta (Aβ) in the neuron and glial cells is mainly located in the atrophic lesions of AD patients [52]. Tau [53]. Disturbance of calcium homeostasis was observed, and calcium-related proteins were proposed to be diagnostic and therapeutic biomarkers in AD [54].…”
Section: Alzheimer's Diseasementioning
confidence: 99%